USING TABLEAU TECHNIQUE TO IMPROVE STUDENTS’ PLOT SUMMARY WRITING ACHIEVEMENT - Desi Tiara (Jurnal Didascein Bahasa, 2018)
The use of Tableau technique in drama class as one of the performance arts has been utilized in recent years. Tableau technique is a kind of technique that allows students to visualize and interpret text in a dramatic pose. The aim of this study was to find out whether or not the use of Tableau technique could improve the students‘ writing achievement, especially in writing plot summary. One group time series design was applied in this study. Thirty students of STBA Methodist Palembang were selected as the participants of this study. The data were collected by using a one-item writing test and were analyzed by using paired sample t-test. The finding of this study showed that the students gained better improvement in their plot summary writing achievement (mean diff=2.267, p=0.000) after using Tableau technique. In conclusion, Tableau technique not only could be applied as one of the performance arts in drama class, but also could be used to improve the students‘ plot summary writing achievement. Keywords: Tableau technique, plot summary.